Gamification and Business Foresight: Design and Impact of an Immersive Escape Room in the Real Estate Sector - Palencia-Triana, César Augusto; Palencia-Alcalá, María Camila (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2025)
In an uncertain business environment, forward-thinking has become an essential strategic skill. This paper presents an escape room designed to raise awareness in a real estate company about the importance of anticipating disruptive changes. Using digital and analogue tools, such as WhatsApp, YouTube and physical objects, an immersive experience was created that promoted reflection on emerging trends in the sector. Gamification and collaborative learning facilitated the transfer of abstract concepts to practical situations. The paper discusses the methodological design, the tools used and the results obtained, proposing this experience as a model for other organizations in their strategic planning.